Beliefs and Businesses: Existence and Value of Current Religious Magazines - Sanpinit, Pattaradhorn; Tansrisook, Sompornnuch (Humanities, Arts and Social Sciences Studies, 2020)
This research aims to analyze the relationship of value and utilization of religious magazines by exploring and studying the compositions of current Buddhist magazines published in Thai between April to September 2019. The study is qualitative in nature, relying on document analysis and content analysis of the selected magazines. The result shows that there are 39 issues, most of which contain folk Buddhism. The visible difference in content between amulet magazines and animist magazines is found in their compositions, i.e., amulet magazines, which mainly deal with small Buddha images and amulet, is composed of color pictures, monk and amulet pictures, amulet advertisement, myths and stories followed by news and activities, coupons, souvenirs (free posters and sacred objects), while animist magazines concern stories of sacred things containing lucky numbers, myths and mysterious stories, monk and amulet pictures, horoscope, amulet advertisements, novels, and coupons respectively. Pictures, souvenirs and coupons are interestingly important compositions in both types of magazines. The compositions of animist and amulet magazines reflect a cycle related to amulet traders, collectors and gamblers. The magazines are the platform providing spaces for advertising beneficial to magazine producers, temples, sacred place and object owners. It is also a great way for amulet buyers and gamblers in pursuit of fortune and relevant information. They are thus still an effective instrument used to encourage religious beliefs and concerning businesses for the specific groups of people.